Antioxidant Activity of a Geopropolis from Northeast Brazil: Chemical Characterization and Likely Botanical Origin. (31st October 2017) - Ferreira, Joselena M.; Fernandes-Silva, Caroline C.; Salatino, Antonio; Message, Dejair; Negri, Giuseppina
Abstract : Geopropolis is a product containing wax, plant resin, and soil particles. It is elaborated by stingless bees of tribe Meliponini. Methanol extracts of sample of geopropolis produced by Scaptotrigona postica ("mandaguari") in the state of Rio Grande do Norte (RN, northeast Brazil) were analyzed for the determination of standard parameters (total phenols, total flavonoids, and radical scavenging activity) and chemical characterization by HPLC-DAD-MS/MS analysis. The sample analyzed has high contents of total phenols and flavonoids, as well as high antioxidant activity. The constituents characterized were mainly flavonols, such as quercetin methyl ethers, and methoxychalcones. Such chemical profile is similar to the composition of a green propolis from the same area of RN, which is produced by Africanized Apis mellifera, using shoot apices of Mimosa tenuiflora, popularly known as "jurema-preta." This finding provides evidence that "mandaguari" geopropolis and honeybee propolis have the same botanical origin in RN. The sharing of a plant resin source by phylogenetically distant bees (Apinae and Meliponinae) suggests that bee genetic factors play little role in the choice of plants for resin collection and that the availability of potential botanical sources plays a decisive role.